Steam Power Plant Powered by Wood Sawdust Waste: A Prototype of Energy Crisis Solution - Hidayah, Fachri; Muslihah, Fitriyyatul; Nuraida, Indri; Winda, Ratu; Vania, V.; Rusdiana, Dadi; Suwandi, Tri; Aziz, Muhammad (Indonesian Journal of Teaching in Science, 2021)
The used of electricity from year to year is increasing. One of the alternative to power plants with abundant availability is wood waste. The aims of this study is to: (1) design a wood waste PLTU prototype as an alternative biomass-based energy resource and an effort to reduce wood waste, (2) describe the calorific value, the resulting electrical voltage, and the duration of the lamp flame generated from wood waste fuel. Teak (Tectona grandis), surian wood waste (Toona sureni), and a mixture of both. This descriptive research includes 3 stages, which is analysis, design, and testing. Through this research, a prototype of a wood waste steam power plant was successfully designed by utilizing biomass waste fuel. The results showed that the calorific value, the resulting electrical voltage, and the resistance time of the lamp varied in the wood samples used. This indicates that the wood samples used have the potential to be used as an alternative to biomass-based energy resources.